Design, Synthesis, QSAR Studies, and Molecular Modeling of Some Novel Bis Methyl 2-[3-(benzo[d]thiazol-2-yl)-2-terephthaloyl-bis-4-oxo-thiazolidin- 5-ylidene]acetates and Screening of their Antioxidant and Enzyme Inhibition Properties - Naseem, Muhammad; Rafique, Hummera; Tayyab, Muhammad; Saeed, Aamer; Mumtaz, Amara (Current Organic Synthesis, 2024)
Introduction: Benzothiazolamine-based bisthiourea precursors were prepared in good yields. These bisthiourea derivatives were cyclized into symmetrical Bis Methyl 2-[3-(benzothiazol- 2-yl)-2-terephthaloyl-bis-4-oxo-thiazolidin-5-ylidene]acetates, by their condensation with (DMAD) dimethyl but-2-meditate in the presence of dry methanol. Materials and Methods: All these compounds were evaluated for their biological applications. Antioxidant activities were performed by adopting a DPPH radical assay, and an in vitro enzyme inhibition assay was performed to investigate their enzyme inhibitory potential against butyrylcholinesterase (BChE) and acetylcholinesterase (AChE). Results: Molecular modeling and QSAR studies were performed to monitor the binding propensity of imidathiazolidinone derivatives with enzymes and DNA. Also, electronic and steric descriptors were calculated to determine the effect of structure on the activity of imidathiazolidinone derivatives. Conclusion: The characterization of all the synthesized compounds was done by their physical data, FT-IR, NMR and elemental analysis.
Keywords: DNA interaction